2002
DOI: 10.1159/000065711
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal, Tracheal and Pulmonary Parenchymal Alterations in Experimental Esophageal Atresia and Tracheoesophageal Fistula

Abstract: Pulmonary complications are among the most important causes of morbidity and mortality in neonates with esophageal atresia and tracheofistula. We aimed to investigate the possible causes of respiratory complications encountered in esophageal atresia (EA) and tracheoesophageal fistula (TEF) in an experimental model. Sprague-Dawley fetal rats treated with adriamycin were used for the experiment. Time mated pregnant rats were given 1.75 mg/kg of adriamicyn intraperitoneally on days 6–9 of gestation. The fetuses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…If the embryologic mechanisms of EA-TEF in infants and rats are similar and the malformations observed in the respiratory tract are identical, it is likely that failures of parenchymal development are also of the same nature in both settings. Previous studies on lung parenchyma in the adriamycin rat model found fairly normal canalicularsaccular patterns (48) and hypoplasia with reduced density of type I pneumocytes (49), although, unfortunately, the authors did not attempt to assess branching or lung mass.…”
Section: Lung Hypoplasia In Esophageal Atresiamentioning
confidence: 99%
“…If the embryologic mechanisms of EA-TEF in infants and rats are similar and the malformations observed in the respiratory tract are identical, it is likely that failures of parenchymal development are also of the same nature in both settings. Previous studies on lung parenchyma in the adriamycin rat model found fairly normal canalicularsaccular patterns (48) and hypoplasia with reduced density of type I pneumocytes (49), although, unfortunately, the authors did not attempt to assess branching or lung mass.…”
Section: Lung Hypoplasia In Esophageal Atresiamentioning
confidence: 99%